Karakteristik fisikokimia dan penerimaan konsumen kopi analog nonkafeina Rhizophora mucronata berdasarkan lama waktu penyangraian: Physicochemical characteristics and consumer acceptance of analogous coffee of non caffeine Rhizophora mucronata based on roasting time - Ningsih, Nita Wahyuni; Pamungkas, Bagus Fajar; Diachanty, Seftylia; Sulistiawati, Septiana; Rusdin, Ilmiani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Analog coffee is a type of non-caffeine coffee that has different content and taste from coffee in general. Rhizophora mucronata mangrove fruit can be used as the main ingredient in making analog coffee because it has a distinctive bitter and slightly astringent taste. The aim of the study was to determine the best roasting time based on physicochemical characteristics and consumer acceptance level. The study used a completely randomized design (CRD) with three different roasting time treatments, namely 30, 45, and 60 minutes, with3 replications. The test results showed that the roasting time treatment had a significant effect on physicochemical characteristics, including yield, moisture content, pH, L*, a*, b*, and degree of whiteness, but had no significant effect on the ash content of R. mucronata mangrove fruit pulp analog coffee. A roasting time of 45 minutes was the best treatment, with a color value of 4.73 (liked), aroma of 3.80 (liked), taste of 5.57 (very liked), and overall 4.70 (liked), moisture content of 4.17%, ash 1.63%, fat 4.93%, protein 7.52%, and carbohydrates 81.11%. The analysis of the coffee analog of R. mucronata mangrove fruit meat revealed the presence of alkaloid, flavonoid, steroid, and triterpenoid compounds, but no saponins or caffeine.